Peran Komitmen Organisasi sebagai Moderasi Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Organisasi Perangkat Daerah di Pemerintah Daerah Indonesia - Evy Nulandari; Linawati Linawati; Erna Puspita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study addresses the issue of inadequate financial reporting by Regional Government Organizations (Organisasi Perangkat Daerah/OPD) in Nganjuk, where financial statements are expected to meet user needs in fulfilling transparency and accountability requirements. The research investigates the influence of four key factors—accounting standards, information systems, internal controls, and the competence of human resources—on the quality of financial statements. Furthermore, it examines the moderating role of organizational commitment in strengthening or weakening the relationships between these factors and financial reporting quality. The study adopts a quantitative research design, with data collected through structured questionnaires distributed to 53 OPD offices, involving 212 randomly selected respondents. Data were analyzed using classical assumption tests to ensure validity and reliability, followed by Moderated Regression Analysis (MRA) employing SPSS software. The findings reveal that information systems, internal controls, and competent human resources have a significant positive effect on the quality of financial reports. In contrast, accounting standards show no significant direct impact. Moreover, organizational commitment plays a moderating role in enhancing the positive effects of information systems, internal controls, and human resource competence on report quality. However, it does not moderate the relationship between accounting standards and financial reporting quality. These results highlight the importance of both technical and human resource aspects in improving financial statement quality within OPDs. While adequate systems and controls are crucial, the study underscores that the presence of strong organizational commitment is a determining factor in maximizing their effectiveness. The research suggests that efforts to improve financial reporting should not only focus on compliance with standards but also on strengthening commitment, training, and the integration of information systems and internal control mechanisms